2022
DOI: 10.3390/ijerph19041997
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Risk Score for Prediction of Life-Threatening Arrhythmia Events in Patients with ST Elevated Acute Coronary Syndrome after Primary Percutaneous Coronary Intervention

Abstract: ST-elevated acute coronary syndrome (STEACS) is a serious condition requiring timely treatment. Reperfusion with primary percutaneous coronary intervention (pPCI) is recommended and preferred over fibrinolysis. Despite its efficacy, lethal complications, such as life-threatening arrhythmia (LTA), are common in post-PCI patients. Although various risk assessment tools were developed, only a few focus on LTA prediction. This study aimed to develop a risk score to predict LTA events after pPCI. A risk score was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…For AMI sick people confounded with cardiogenic shock, sophisticated heart failure, or malfunctioned reperfusion, mechanical support devices like as percutaneous cardiopulmonary support and intra-aortic balloon pumping are essential in relation to interventional therapy. As a result, AMI sufferers who need mechanical assistance devices are regarded as a category of higher risk acute myocardial infarction sufferers who have a high rate of fatality while hospitalized (Wongthida et al, 2022). Recent studies have shown that repeat acute myocardial infarction people receiving primary PPCI, a diverse group of higher risk AMI patients, had an in-hospital death that was considerably higher compared to that of 1st AMI patients, as well as the factors that determined in-hospital consequences in recurrent AMI sufferers who undergo PPCI were distinctive from those who determined in-hospital consequence in 1st AMI patients (Corpus et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For AMI sick people confounded with cardiogenic shock, sophisticated heart failure, or malfunctioned reperfusion, mechanical support devices like as percutaneous cardiopulmonary support and intra-aortic balloon pumping are essential in relation to interventional therapy. As a result, AMI sufferers who need mechanical assistance devices are regarded as a category of higher risk acute myocardial infarction sufferers who have a high rate of fatality while hospitalized (Wongthida et al, 2022). Recent studies have shown that repeat acute myocardial infarction people receiving primary PPCI, a diverse group of higher risk AMI patients, had an in-hospital death that was considerably higher compared to that of 1st AMI patients, as well as the factors that determined in-hospital consequences in recurrent AMI sufferers who undergo PPCI were distinctive from those who determined in-hospital consequence in 1st AMI patients (Corpus et al, 2004).…”
Section: Introductionmentioning
confidence: 99%